Penerapan Model Pembelajaran Bambo Dancing Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Akidah Akhlak Siswa Kelas VIII Di MTS N 1 Langkat - Amrul Al Azmi, Muhizar Muchtar, Ahmad Fuadi (Jurnal Pusat Studi Pendidikan Rakyat, 2023)
This study aims to determine the Learning Outcomes of students in Akidah Akhlak learning after the application of the Bambo Dancing Learning Model in class VIII MTs N 1 Langkat. This research is included in class action research (Action Research). This research uses a type of collaborative model, namely researchers with Fiqh study teachers in class VIII MTs N 1 Langkat. The subjects in Class Action Research VIII are students of class VIII MTs N 1 Langkat with a total of 32 students. the instruments in this researcher are observation sheets and tests in accordance with the research procedures by observing cycle I and cycle II. Student learning outcomes in Akidah Akhlak subjects before using the Bambo Dancing model are still relatively low or below the KKM standard. This can be seen from the students' scores, namely out of 32 only 13 students 40.62% who obtained a score ? 75 or who met the KKM score. Whereas in this study it can be declared classically complete if the completeness of student learning outcomes reaches 85%.The application of the Bambo Dancing learning model can be implemented well through two cycles. This can be seen through the activities carried out by teachers and students in cycle I and cycle II have increased. The results of teacher observations in cycle I were 72.5 then became 89.28 (good) in cycle II. Likewise, the observation of student activities which initially in cycle I reached a score of 72.5 then increased to 87.5 in cycle II. After the application of the Bambo Dancing learning model, student learning outcomes have increased, this can be seen from the results of the pre-cycle learning test which only reached an average score of 66.71 (less) and increased in cycle I to 72.96% (sufficient) and in cycle II increased again to 85.31% (good). The improvement in learning outcomes can also be seen in the increase in the percentage of student completeness, namely in the pre-cycle only 40.62% while in cycle I it reached 65.62% and in cycle II it was 87.5%. Therefore, it is concluded that the use of the Bambo Dancing model can improve student learning outcomes.